A new species of Selaginella (Selaginellaceae) from the Bolsovian (Carboniferous Period) of the Zonguldak – Amasra Coal Basin, north-western Turkey - Zbynek Šimunek; Barry A. Thomas (Geologia Croatica, 2012)
Shoot fragments of a new species of Selaginella Beauv are described from the Bolsovian (Carboniferous Period) of Amasra, Turkey. The shoots are heterophyllous with three paired ranks of different sized leaves enabling it to be referred to the subgenus Hexaphyllum THOMAS. The size, shape and epidermal details of the leaves enable it to be differentiated from other Pennsylvanian species and referred to a new species Selaginella amasrae ŠIMŮNEK & THOMAS, sp. nov. This new record extends the early distribution of the subgenus suggesting that it first appeared in eastern Variscan Euramerica and the intermontane basins of central Europe, before spreading into the foreland basins of western Euramerica.